Protestantismo e golpe militar de 1964 em Pernambuco: uma análise da cruzada de ação básica cristã - Lima Junior, José Ferreira de (2008)
The military coup of 1964 indicated a genuine political retreat in the movement for a just and fraternal society, because it established a dictatorial and antidemocratic regime. Protestant groups began to support it. In doing so they were embracing a denial of democratic and christian values, since these very churches, by defending the theory of protestant ideology, based on liberty and free will, became themselves authoritarian and repressive, treating those opposed to the new regime as enemies without the due process of law. The March of the Family with God for Freedom, in Recife, meant that the support of protestant and catholic religious groups for the military coup of 1964, were actually threatening the preservation of christian and democratic values. People in leadership of protestant and catholic churches joined against a common enemy: communism. In this context we study the Crusade of Christian Basic Action (Cruzada ABC), a protestant educational movement of youths and adults, sustained by an agreement among USAID, the Colégio Agnes Erskine of Recife, and SUDENE, which alleged to be philanthropic. We emphasize the religious content and proselytism of the Cruzada ABC, inspired by the social values of the United States